Booth Etiquette - Azizbek qizi, Odiljonova Sarvinoz (European Journal of Life Safety and Stability (2660-9630), 2021)
Stand up, smile, and make eye contact. Greet attendees inside and in front of the entrances of the booth. Speak with attendees, not colleagues or on your phone. Keep it short and simple and engage your prospects in conversation. Research shows that trade show attendees weigh their interaction with staff over every other factor at the booth. Why then is staff training often the smallest spending segment in marketing budgets? The Center for Exhibition Industry Research (CEIR) reported that, on average, booth staff training was as little as 1% of total trade show budget in 2012. That figure was still only 2% in 2017! This guide looks at why you will want to invest in staff training and areas to apply that investment. A well-trained staff will be one of the most significant factors in the success (or failure) of your booth. Whether your company is planning for a mere 10’ by 10’ booth or a large 40’ by 50’ trade show exhibit space, training the staff who will be manning the booth during the show itself is of the utmost importance.